MEG LOWMAN SHARING HER PASSION FOR THE SCIENCE OF THE TREETOPS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 5 October 2016 “ Forests are critical to our health,” said Professor Dr. Margaret “Meg” Lowman in her keynote address at the 1 Symposium on the Study of the Biodiversity at Penang Hill, held at the Dewan Persidangan Universiti, Universiti Sains Malaysia (USM) today.